Factors Related to Home Self-Care Behavior in the Elderly with Osteoarthritis in Wat Salud Community, Bang Phil District, Samut Prakarn Province - Jitdorn, Jurawan; Chaorai, Sasitorn; Tangpitakkun, Jeeraphat; Kruamen, Apaphat; Thiphanrangsarit, Onpreeya; Gunman, Suwanan; Janrueng, Jantarat; Wichapanit, Suchada; Jamreanlap, Marisa (Journal of Health Sciences and Wellness, 2020)
This descriptive cross-sectional design aimed to study the severity of osteoarthritis, home self-care behavior of osteoarthritis and factors related to home self-care behaviors in 40 elderly with osteoarthritis, Wat Salud Community, Bang Phil District, Samut Prakarn Province. Research tools included: Personal information questionnaire, health status questionnaire, evaluation of the severity of osteoarthritis (Oxford knee score) and self-care behavior questionnaire for the elderly with osteoarthritis. The research instruments were content validated by 3 nursing experts. The content validity index was 1. The Cronbach's alpha coefficient was 0.76, 0.76, 0.87, 0.80, respectively. Data were analyzed using frequency, percentage, mean, standard deviation and chi-square statistics. The results showed that 30% of the subjects had a moderate level of osteoarthritis followed by 25% of them with severe pain and having initial osteoarthritis symptoms. It was found that 77.5% of the subjects had home self-care behaviors that were at a moderate level. The body mass index was significantly correlated with the self-care behaviors of the elderly with osteoarthritis.